Visualization of 40 Years of Tropical Cyclone Positions and Their Rainfall Impacts in Central America - Hernández Castro, Franklin (2021)
Correos de investigadores: franhernandez@itcr.ac.cr || jomonge@itcr.ac.cr || hugo.hidalgo@ucr.ac.cr || erick.alfaro@ucr.ac.cr